2021
DOI: 10.1155/2021/2080962
|View full text |Cite
|
Sign up to set email alerts
|

Association of Iris Structural Measurements with Corneal Biomechanics in Myopic Eyes

Abstract: Purpose. To evaluate the relationship between iris sectional parameters on swept-source optical coherence tomography (SS-OCT) with corneal biomechanics measured by Corneal Visualization Scheimpflug Technology (Corvis ST) in young adults with myopia. Methods. 117 patients with myopia aged ≥18 years were recruited from the Eye Hospital of Wenzhou Medical University, who had complete SS-OCT and Corvis ST data. Only the left eye of each participant was selected for analysis. Iris sectional parameters included iris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… 37 39 It has also been reported that corneal biomechanical properties are related to retinal deformation 40 and iris sectional parameters. 41 , 42 This may be due to the deformation of the sclera, which dominates the eyeball nonuniform deformation, leading to corneal mechanical properties connected with other tissue characteristics.…”
Section: Discussionmentioning
confidence: 99%
“… 37 39 It has also been reported that corneal biomechanical properties are related to retinal deformation 40 and iris sectional parameters. 41 , 42 This may be due to the deformation of the sclera, which dominates the eyeball nonuniform deformation, leading to corneal mechanical properties connected with other tissue characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…High myopia is more likely to be accompanied by structural abnormalities of the anterior chamber, such as deep anterior chamber depth and concave iris [ 6 ]. Concave iris is a typical characteristic of pigment dispersion syndrome [ 7 ].…”
Section: Introductionmentioning
confidence: 99%